Transcription of Endogenous Retrovirus Group K Members and Their Neighboring Genes in Chicken Skeletal Muscle Myoblasts - Tomohide Takaya; Yuma Nihashi; Tamao Ono; Hiroshi Kagami (The Journal of Poultry Science, 2021)
Skeletal muscle myoblasts are myogenic precursor cells that generate myofibers during muscle development and growth. We recently reported that broiler myoblasts, compared to layer myoblasts, proliferate and differentiate more actively and promptly into myocytes, which corresponds well with the muscle phenotype of broilers. Furthermore, RNA sequencing (RNA-seq) revealed that numerous genes are differentially expressed between layer and broiler myoblasts during myogenic differentiation. Based on the RNA-seq data, we herein report that chicken myoblasts transcribe endogenous retrovirus group K member (ERVK) genes. In total, 16 ERVKs were highly expressed in layer myoblasts and two (termed BrK1 and BrK2) were significantly induced in broiler myoblasts. These transcribed ERVKs had a total of 182 neighboring genes within ±100 kb on the chromosomes, of which 40% were concentrated within ±10 kb of the ERVKs. We further investigated whether the transcription of ERVKs affects the expression of their neighboring genes. BrK1 had two neighboring genes; LOC107052719 was overlapping with BrK1 and downregulated in the broiler myoblasts, and FAM19A2 was upregulated in the broiler myoblasts as well as BrK1. BrK2 had 14 neighboring genes, and only one gene, LOC772243, was differentially expressed between layer and broiler myoblasts. LOC772243 was overlapping with BrK2 and suppressed in the broiler myoblasts. These data indicate that the transcription of ERVKs may impact the expression of their neighboring genes in chicken myoblasts.